Negotiating territoriality
1 online resource (ix, 255 pages)
Keywords: "This edited collection disrupts dominant narratives about space, states, and borders, bringing comparative ethnographic and geographic scholarship in conversation with one another to illuminate the varied ways in which space becomes socialized via political, economic, and cognitive appropriation. Societies must, first and foremost, do more than wrangle over ownership and land rights -- they must dwell in space. Yet, historically the interactions between the state's territorial imperative with previous forms of landscape management have unfolded in a variety of ways, including top-down imposition, resistance, and negotiation between local and external actors. These interactions have resulted in hybrid forms of territoriality, and are often fraught with fundamentally different perceptions of landscape. This book foregrounds these experiences and draws attention to situations in which different social constructions of space and territory coincide, collide, or overlap. Each ethnographic case in this volume presents forms of territoriality that are contingent upon contested histories, politics, landscape, the presence or absence of local heterogeneity and the involvement of multiple external actors with differing motivations -- ultimately all resulting in the potential for conflict or collaboration and divergent implications for conceptions of community, autochthony and identity"--